Prospective pilot study of fully covered self-expandable metal stents for refractory benign pancreatic duct strictures: long-term outcomes - Matsubara, Saburo; Sasahira, Naoki; Isayama, Hiroyuki; Takahara, Naminatsu; Mizuno, Suguru; Kogure, Hirofumi; Yamamoto, Natsuyo; Nakai, Yousuke; Tada, Minoru; Koike, Kazuhiko (Endoscopy International Open, 2016)
Background and study aims: Background and study aims: Temporary placement of a fully covered self-expandable metal stent (FCSEMS) has recently emerged as a treatment option for pancreatic duct strictures due to chronic pancreatitis refractory to conventional plastic stenting. However, there are no data about long-term outcomes with this therapeutic option. The aims of the current study were to estimate the feasibility, safety, efficacy, and long-term outcomes of temporary FCSEMS placement for refractory pancreatic duct strictures.Patients and methods: This was a prospective, single-center feasibility study. Ten patients with refractory pancreatic duct strictures due to chronic pancreatitis underwent FCSEMS placement for 3 months. We evaluated the rate of recurrent symptoms after stent removal during long-term follow-up, as well as adverse events (AEs).Results: Two patients required early (within 1 week) stent removal because of intolerable pain or pancreatitis. In the remaining 8 patients, the recurrence rate of any symptoms after FCSEMS removal was 63% during 35 months of follow up. The causes of recurrent symptoms were as follows: recurrence of stricture in 2; stent-induced stricture in 1; impaction of pancreatic stones in 1; and development of a pseudocyst in 1. When limited to stricture, the recurrence rate was 38%. Additional endoscopic treatments were required in 4 patients: a second FCSEMS placement in 1; plastic stent (PS) placement in 1; stone extraction in 1; and endoscopic ultrasound–guided pseudocyst drainage in 1. Asymptomatic stent migration occurred in 2 patients. Suppurative pancreatic ductitis due to food impaction in the FCSEMS occurred in 2 patients, and endoscopic pancreatic duct drainage was performed. Stent-induced ductal changes developed in 2 patients and PS treatment was required in 1 patient for pain relief.Conclusion: The FCSEMS appears to be a feasible and potentially effective option for the management of refractory pancreatic duct strictures due to chronic pancreatitis during long-term follow-up. AEs including post-procedure pain, stent-induced ductal changes, migration, and ductitis are issues that need to be resolved.